Chimeric Fusion (F) and Attachment (G) Glycoprotein Antigen Delivery by mRNA as a Candidate Nipah Vaccine - Loomis, Rebecca J.; DiPiazza, Anthony T.; Falcone, Samantha; Ruckwardt, Tracy J.; Morabito, Kaitlyn M.; Abiona, Olubukola M.; Chang, Lauren A.; Caringal, Ria T.; Presnyak, Vladimir; Narayanan, Elisabeth; Tsybovsky, Yaroslav; Nair, Deepika; et al. (Frontiers in Immunology, 2021)
Nipah virus represents a significant pandemic threat with zoonotic transmission from bats-to-humans with almost annual regional outbreaks characterized by documented human-to-human transmission and high fatality rates. Currently, no vaccine against NiV has been approved. Structure-based design and protein engineering principles were applied to stabilize the fusion (F) protein in its prefusion trimeric conformation (pre-F) to improve expression and increase immunogenicity. We covalently linked the stabilized pre-F through trimerization domains at the C-terminus to three attachment protein (G) monomers, forming a chimeric design. These studies detailed here focus on mRNA delivery of NiV immunogens in mice, assessment of mRNA immunogen-specific design elements and their effects on humoral and cellular immunogenicity. The pre-F/G chimera elicited a strong neutralizing antibody response and a superior NiV-specific Tfh and other effector T cell response compared to G alone across both the mRNA and protein platforms. These findings enabled final candidate selection of pre-F/G Fd for clinical development.